Gender‐Specific Body Areas Satisfaction and Body Weight Status in Adolescents: Mediating Effects of Physical Activity, Fruit and Vegetable Intake, and Energy‐Dense Food Intake. Issue 1 (5th October 2018) - Zarychta, Karolina; Chan, Carina K.Y.; Kruk, Magdalena; Luszczynska, Aleksandra
Abstract : Background: Body satisfaction is one of the key modifiable cognitive determinants of eating behaviours, physical activity, and body mass index (BMI). As the sociocultural models suggest, low body satisfaction may explain unhealthy eating and exercise behaviours. Importantly, body satisfaction levels and body areas that individuals focus on vary across genders. This study aims at investigating links between the global index of body areas satisfaction (BAS), gender‐specific BAS, fruit and vegetable (F&V) intake, energy‐dense foods intake, moderate‐to‐vigorous physical activity (MVPA), and BMI. Methods: In all, 1, 254 adolescents completed questionnaires and had their weight and height objectively measured with 2‐ and 13‐month follow‐ups. Indirect effects of three indices of BAS were tested in three models (male‐specific BAS amongst boys; female‐specific BAS amongst girls; the global BAS index in the total sample). Results: Higher levels of all three BAS indices indirectly predicted lower BMI, with higher MVPA mediating this effect. In addition, higher energy‐dense foods intake mediated higher global BAS–higher BMI relationship in the total sample. Thus, the global index of BAS acts as double‐edged sword, predicting both higher MVPA and energy‐dense foods intake. Conclusion: BAS may operate in a complex manner, predicting behaviours which may have opposite effects on BMI.